Intergenerational transmission of economic success in Austria with a focus on migration and gender - Daniel Reiter; Mario Thomas Palz; Margareta Kreimer (Journal for Labour Market Research, 2020)
In this paper, we analyse the intergenerational transmission of economic success in Austria using the European Union Statistics on Income and Living Conditions 2011 dataset (EU-SILC 2011). Starting point of the investigation is a two-step estimation procedure, where we detect a significant positve intergenerational association between the eco-nomic situation of the parental household and educational attainments as well as gross hourly wages of their male and female descendants independently. Furthermore, we shed some light on the intergenerational social mobility black box by explaining the direct effect of the income situation of the parental generation on attainable wages of the child generation within the transmission system. It turns out that this effect is significantly underestimated when applying ordinary least squares regressions only, where the perceived socioeconomic status is taken exogenous. Finally, we apply instrumental variable quantile regressions to demonstrate that the direct intergenerational economic association between parents and their descendants is strongest for top earners. Alongside this proceeding, we intro-duce an alternative way to think about the impact of a bundle of additional intergenerational transmission channels like cognitive ability, noncognitive personal traits, and aspects of physical appearance on an empirical level. Overall, the findings of the paper, where special attention is paid to migrants, offer a better understanding on the intergenera-tional transmission of economic success mechanism and to what extent this process influences income persistence between generations.
Keywords: C36; J15; J16; J31; J62; J68; 330; Intergenerational social mobility; Gender; Migrants; Labour market; Instrumental variable quantile regression